The philosopher responds : an intellectual correspondence from the tenth century. Volume two - Abū Ḥayyān al-Tawḥīdī, ʻAlī ibn Muḥammad, active 10th century; Ibn Miskawayh, Aḥmad ibn Muḥammad, -1030; Stewart, Devin J.; Urfahʹlī, Bilāl; Pomerantz, Maurice A.; Vasalou, Sophia; Montgomery, James E. (James Edward), 1962- (New York : New York University Press, 2019)
Questions and answers from two great philosophersWhy is laughter contagious? Why do mountains exist? Why do we long for the past, even if it is scarred by suffering? Spanning a vast array of subjects that range from the philosophical to the theological, from the philological to the scientific, The Philosopher Responds is the record of a set of questions put by the litterateur Abu Hayyan al-Tawhidi to the philosopher and historian Abu 'Ali Miskawayh. Both figures were foremost contributors to the remarkable flowering of cultural and intellectual life that took place in the Islamic world during the reign of the Buyid dynasty in the fourth/tenth century. The correspondence between al-Tawhidi and Miskawayh holds a mirror to many of the debates and preoccupations of the time and reflects the spirit of rationalistic inquiry that animated their era. It also provides insight into the intellectual outlooks of two thinkers who were divided as much by their distinctive temperaments as by the very different trajectories of their professional careers. Alternately whimsical and tragic, wondering and brooding, trivial and profound, al-Tawhidi's questions provoke an interaction as interesting in its spiritedness as in its content. This new edition of The Philosopher Responds is accompanied by the first full-length English translation of this important text, bringing this interaction to life for the English reader.
On why people seek likenessesOn why we find it easier to represent extreme ugliness in our imagination than exquisite beauty; On why sudden joy affects people so violently; On why we experience states of suffering more intensely than states of well-being; On why seeing someone laughing causes others to laugh; On why human beings are so attached to the world despite the misfortunes and suffering they experience in it; On why people say the world would fall to ruin if it weren't for fools; On the anxiety experienced by people who have something to hide
On why we are more likely to heed a preacher who practices what he preaches
Online resource; title from digital title page (viewed on November 13, 2019).
Print version record.
In English.
eBooks on EBSCOhost
Keywords: Abū Ḥayyān al-Tawḥīdī, ʻAlī ibn Muḥammad, -- active 10th century; Ibn Miskawayh, Aḥmad ibn Muḥammad, -- -1030.; Ibn Miskawayh, Aḥmad ibn Muḥammad, -- -1030 -- Correspondence; Abū Ḥayyān al-Tawḥīdī, ʻAlī ibn Muḥammad, -- active 10th century -- Correspondence; Ibn Miskawayh, Ahmad ibn Muhammad, -- -1030 -- Correspondence; Abū Hayyān al-Tawhīdī, ʻAlī ibn Muhammad, -- active 10th century -- Correspondence; Authors, Arab -- To 1258 -- Correspondence; Philosophers -- Iran -- 10th century -- Correspondence; Islamic philosophy -- Early works to 1800.; Écrivains arabes -- Jusqu'à 1258 -- Correspondance; Philosophes -- Iran -- 10e siècle -- Correspondance; Philosophie islamique -- Ouvrages avant 1800.; PHILOSOPHY -- General; Authors, Arab; Islamic philosophy; Philosophers; Iran; Islamic philosophy -- Early works to 1800.; Philosophers -- Iran -- 10th century -- Correspondence; Authors, Arab -- To 1258 -- Correspondence; To 1258; Early works; Personal correspondence